2021
DOI: 10.1007/s10072-021-05757-3
|View full text |Cite
|
Sign up to set email alerts
|

Pontocerebellar atrophy is the hallmark neuroradiological finding in late-onset Tay-Sachs disease

Abstract: Purpose Late-onset Tay-Sachs disease (LOTS) is a form of GM2 gangliosidosis, an autosomal recessive neurodegenerative disorder characterized by slowly progressive cerebellar ataxia, lower motor neuron disease, and psychiatric impairment due to mutations in the HEXA gene. The aim of our work was to identify the characteristic brain MRI findings in this presumably underdiagnosed disease. Methods Clinical data and MRI findings from 16 patients (10F/6 M) with LOTS from two centers were independently assessed by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The morphometric analysis confirmed the finding of pontocerebellar atrophy in accordance with our earlier published results based on manual semiquantitative measurements 11 . With almost 60% of new patients, the present dataset can be considered to mostly not overlap with the previous study, so the finding of pontocerebellar atrophy was confirmed in a largely independent cohort.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The morphometric analysis confirmed the finding of pontocerebellar atrophy in accordance with our earlier published results based on manual semiquantitative measurements 11 . With almost 60% of new patients, the present dataset can be considered to mostly not overlap with the previous study, so the finding of pontocerebellar atrophy was confirmed in a largely independent cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, many LOTS patients retrospectively report being clumsy during childhood, long before they seek neurologic care 41 . The relatively weak association between the severity of ataxia and cerebellar atrophy reported previously 11,41 and also shown in our current study suggests that the occurrence of prominent ataxia in the disease course may be linked not only to progression of cerebellar degeneration but also to the loss of compensatory mechanisms or lesion of ascending spinocerebellar pathways.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…This low prevalence, may be related to visually assessing scans, as opposed to detailed, quantitative measurements, particularly as Májovská et al. suggested that pontocerebellar atrophy may represent a cornerstone of imaging diagnosis in LOTS 32 . The presence of brainstem neuropathological abnormalities has been variable across limited pathological studies 4,6,7 .…”
Section: Discussionmentioning
confidence: 99%